PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI NEGERI PEMERINTAH KABUPATEN KONAWE SELATAN PROVINSI SULAWESI TENGGARA - Sugito Efendi; Almansyah Rw (Jurnal Ilmu dan Budaya, 2015)
The analysis showed that organizational culture, leadership style and motivation have a positive and direct impact on employee performance. The result of determination cooficients is 0,761 or 76,1 percent. This empirical result indicated that in order to satisfy and improve the performance of staff of the Regional Government of Konawe Selatan, need to consider the factors of organizational culture, leadership style and motivation, because these factors are shown to affect the level of employee performance.